Effects on Trout Alevins of Chronic Exposures to Chemically Dispersed Access Western Blend and Cold Lake Blend Diluted Bitumens. (12th June 2020) - Adams, Julie E.; Madison, Barry N.; Charbonneau, Kelli; Sereneo, Marie; Baillon, Lucie; Langlois, Valerie S.; Brown, R. Stephen; Hodson, Peter V.
Abstract: The present study assessed the chronic toxicity of 2 chemically enhanced water accommodated fractions (CEWAFs) of diluted bitumens (dilbits), Access Western Blend (AWB) and Cold Lake Blend (CLB), to rainbow trout alevins. Chemical dispersion was used to overcome the resistance to dispersion of dilbits and to generate test solutions that contained more and smaller oil droplets for increased partitioning of petroleum hydrocarbons into water. Test solutions were characterized by fluorescence spectroscopy, a rapid and inexpensive analytical tool to compare toxicity endpoints measured by fluorescence (total petroleum hydrocarbons measured by fluorescence [TPH‐F]). Cumulative mortality and the prevalence and severity of malformations increased following exposure of alevins to dispersed dilbits. Toxicity curves overlapped for AWB and CLB when expressed as TPH‐F and 22‐ to 24‐d median lethal and effect concentrations ranged from 0.36 to 1.5 mg/L. Gene expression in alevins was also altered following exposure to dispersed dilbit, with relative cytochrome P450‐1A mRNA levels increasing up to 170‐fold for AWB and up to 240‐fold for CLB. Access Western Blend and CLB caused similar toxicity to rainbow trout alevins as light to medium conventional crude oils, and rainbow trout alevins were more sensitive than yellow perch, Japanese medaka, and fathead minnow embryos exposed to dispersed AWB and CLB. The present study is the first to assess the embryotoxicity of dilbits to a Canadian freshwater salmonid species. Environ Toxicol Chem 2020;39:1620–1633. © 2020 SETAC Abstract : The toxicity of chemically dispersed dilbit to rainbow trout alevins is similar to that of light to medium conventional crude oils. AWB = Access Western Blend; CEWAF = chemically enhanced water accommodated fraction; CLB = Cold Lake Blend; LC50 = median lethal concentration; TPH‐F = total petroleum hydrocarbons measured by fluorescence.